CORRELATION SELF-EFFICACY DENGAN PERFORMA SISWA EKSTRAKURIKULER FUTSAL SMA NEGERI 1 SEBERIDA - Kharis Nurdiansyah; Agus Sulastio; Ni Putu Nita Wijayanti (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
Psychological factors are now an important factor in sports, including futsal. Each research activity certainly has a purpose and objective based on the formulation of the problem that has been formulated by the researcher. And this study is intended to determine whether there is a correlation between self-efficacy and the performance of futsal extracurricular students at SMA Negeri 1 Seberida, using 10 students who take part in futsal extracurriculars as a sample with a sampling technique that is purposive sampling and using an instrument in the form of a questionnaire for the self-efficacy variable. and futsal basic skills tests for performance variables. To analyze the data, the researcher used IBM SPSS software version 23 with Pearson product moment correlation analysis. The results of the study prove that there is a significant correlation between self-efficacy and the performance of futsal extracurricular students at SMA Negeri 1 Seberida as evidenced by the value (rcount = 0.999 > rtable = 0.632) and the significance value of Sig.(2-tailed) is sig.count. = 0.000 < sig.table = 0.05. The conclusion in this study is that there is a significant correlation between self-efficacy and the performance of futsal extracurricular students at SMA Negeri 1 Seberida.